Proceedings of the 35th IEEE Conference on Decision and Control (IEEE, 1997)
Theory and application of systems design to industrial and process industries are discribed. Advance research for industrial improvement is reported. Optimization techniques of established processes and industries are extended to new fields
Keywords: Konferenzschrift